2022
DOI: 10.3389/fimmu.2022.840272
|View full text |Cite
|
Sign up to set email alerts
|

Rotenone Modulates Caenorhabditis elegans Immunometabolism and Pathogen Susceptibility

Abstract: Mitochondria are central players in host immunometabolism as they function not only as metabolic hubs but also as signaling platforms regulating innate immunity. Environmental exposures to mitochondrial toxicants occur widely and are increasingly frequent. Exposures to these mitotoxicants may pose a serious threat to organismal health and the onset of diseases by disrupting immunometabolic pathways. In this study, we investigated whether the Complex I inhibitor rotenone could alter C. elegans immunometabolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…Interestingly, AUDDIT revealed that worms exposed to 0.03 µM rotenone have shorter dendrites than controls (Fig 3C). We hypothesize that this is due to rotenone slowing development in worms, and thus making the dendrites shorter(46). The worms exposed to 0.5 µM rotenone were grown for an extra day to account for slower development, which permitted the dendrites enough time to reach the same length as the controls.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, AUDDIT revealed that worms exposed to 0.03 µM rotenone have shorter dendrites than controls (Fig 3C). We hypothesize that this is due to rotenone slowing development in worms, and thus making the dendrites shorter(46). The worms exposed to 0.5 µM rotenone were grown for an extra day to account for slower development, which permitted the dendrites enough time to reach the same length as the controls.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, a shift towards G3P and succinate oxidation was observed suggesting that functional suppression complex I-dependent OXPHOS is linked to immune activation (Cormier et al, 2022). In C. elegans, while strong inhibition of complex I activates innate immune response and prevents neurodegeneration (Chikka et al, 2016), mild rotenone treatment down-regulated the expression of immune response genes, rendering roundworms prone to bacterial infections (Mello et al, 2022). In summary, we demonstrate that activation of innate immunity is strongly associated with reduced flight muscle complex I activity with direct consequences to mitochondrial proline oxidation and flight activity.…”
Section: Discussionmentioning
confidence: 99%
“…From the evolutive perspective, functional associations between complex I and immunity were reported for invertebrate organisms (Chikka et al, 2016; Cormier et al, 2022; Mello et al, 2022). In this sense, specific complex I-driven OXPHOS associates with increasing defensin expression in honeybees during winter (Cormier et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that norharman and harman could disturb the metabolism of compounds in nematodes by changing the expressions of genes that regulate the key enzymes in phase II reactions, ultimately inducing neurotoxicity. 42…”
Section: Food and Function Papermentioning
confidence: 99%